Analisis Strategi Pemasaran Islami Dalam Meningkatkan Daya Beli Ayam Bakar Santoso Binjai - Cahyani, Serina Regita; Hendra, Hendra (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the Islamic marketing strategies implemented by Ayam Bakar Santoso in Binjai and examine their contribution to increasing consumers’ purchasing power. This research employs a qualitative field approach with a descriptive-analytical design. Data were collected through in-depth interviews, direct observation, and documentation involving the business owner, employees, and customers. The findings reveal that Islamic marketing strategies are reflected in the application of honesty (shiddiq), trustworthiness (amanah), transparent pricing, ethical and courteous service, commitment to product quality and cleanliness, and non-manipulative promotional practices. These principles significantly build customer trust, satisfaction, and loyalty, which ultimately encourage repeat purchases and sustainable purchasing power growth. The study also shows that purchasing decisions are influenced not only by price and taste but also by emotional experiences, perceived fairness, and moral values embedded in the transaction process. The novelty of this research lies in its in-depth qualitative analysis of Islamic marketing practices within a local micro-scale culinary business, emphasizing the integration of the owner’s spiritual orientation and social brotherhood (ukhuwah) values as strategic factors that strengthen sustainable consumer purchasing behavior.